Age-friendly communities for older persons with intellectual disabilities. (25th October 2019) - Miskimmin, Caley; Shooshtari, Shahin; Menec, Verena; Duncan, Karen A.; Martin, Toby; Stoesz, Brenda M.
Abstract : Purpose: The life expectancy for persons with intellectual disabilities (ID) has increased significantly, resulting in an increasing number of aging persons with ID. To promote healthy and active aging of persons with ID, discussions on new initiatives to design age-friendly communities have begun at local and international levels. The purpose of this paper, a qualitative research study, is to identify features of an age-friendly community, and facilitators and barriers from the perspectives of older adults with mild ID and their caregivers who live in the city of Winnipeg in Canada. Design/methodology/approach: Seven older persons with mild ID were interviewed, and 15 caregivers participated in focus group discussions. All participants were asked questions about features of community living and their experiences in eight broad topic areas (i.e. transportation, housing, social participation, respect and social inclusion, opportunities for community involvement, communication and information, community support and healthcare services, and outdoor spaces and buildings). Findings: The results indicated that many of the current features of the city of Winnipeg do not adequately address the needs of aging persons with ID; specifically, participants revealed that issues related to accessibility, social participation, social disrespect and inclusion, and lack of resources were important barriers to independence. Originality/value: The findings will increase awareness of the needs of aging persons with ID and inform programme planning, service delivery, coordination of community-based services and policies to support healthy and active aging for this vulnerable population.